Influencing factors of social commerce behavior in Saudi Arabia - Mohamed Razi, Mohamed Jalaldeen; Sarabdeen, Masahina; Mohd Tamrin, Mohd Izzuddin; Kijas, Abdul Cafoor Muhammadu (IEEE, 2019)
Social commerce is getting popular all over the world including in the middle eastern countries. The main objective of this work is to identify the factors that influence the purchasing intention and the behavior among the Y generation and millennials in the Kingdom of Saudi Arabia. For this purpose, a hypothetical conceptual model was developed based on proven theories and well-established literature. To test this model, data were collected from 178 university students using an online questionnaire. Data were analyzed using SPSS 25. The validity and the reliability of the questionnaire items were determined through factors analysis and Cronbach Alpha. All hypotheses were supported in linear regression analysis, however, the stepwise multiple regression analysis which shows the simultaneous effects of the independent variables, resulted in that out of 11 hypotheses 3 were not supported. Based on the findings a discussion was developed at the end of the paper.